Conflict modelling and resolution : the case of the Bangkok Mass Transit System Project - Janevit Siriassakul; Pastijn, Hugo; Tabucanon, Mario T.; Tang, John C.S.; The Federal Republic of Germany (DAAD) (Bangkok : Asian Institute of Technology, 1994)
A conflict is a situation in which there is a condition of opposition, and parties with opposing goals affect one another. The objective of conflict analysis is to predict the most likely resolution for the conflict. The first step in performing conflict analysis is to select a point in time. This is extremely important since a conflict is a dynamic phenomenon and its components may change over the courses of conflict. Typically, a conflict can be modeled as a hierarchical structure which consists of three main components: players; objectives; and options. In this study, a conflict of the Bangkok mass transit system is examined. Since on May 17, 1994, the cabinet had decided that all mass transit systems within an inner city area must go underground. The resolution had affected the three mass transit projects: Hopewell's; Bangkok Transit System Corporation (BTSC)'s; and Muang Thong Mass Transit (MTMT)'s projects. According to conflict of taking parts of the three projects underground, the BTSC's mass transit project is selected as a case study. The point in time to conduct conflict analysis is July 12, 1994 the date the government have to make a decision to solve the conflict. This conflict may lead to legal problems with BTSC and affect investment climate to the country. The methodology using to conduct conflict analysis consists of two methods: the conflict analysis method (Fraser and Hipel, 1979); and the AHP forward process. The conflict analysis method works well in practice and its assumptions reflect closely what happens in reality. The objective of the conflict analysis method is to predict the potential resolutions or equilibria for the conflict. However, the conflict analysis method has no clearly approach to specify which one of these equilibria be the most likely resolution. This disadvantage can be compensated by applying the AHP forward process. The AHP forward process is applied to project forward the most likely resolution to happen, given the objectives and capabilities of each player to the conflict. Therefore, the application of the conflict analysis method complimented with the AHP forward process, is perfectly to conduct conflict analysis. In addition to the conflict analysis method, the concept of Pareto optimality is applied to specify which equilibria be the non-dominated or Pareto ones, and a sensitivity analysis technique is applied to assess the possible range of the potential resolutions. For the AHP forward process, the two sensitivity analysis techniques adding with a non parametric statistics named Mann Whitney test, are applied to test for the reliability of the solution as well as its stability in future. Consequently, regarding the conflict of BTSC's mass transit project, the analysis results are closely same to the evidences happened in the real world conflict. According to all the concepts applied in this study, finally a general integrated framework for conflict analysis is introduced.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Conflict management